Learning Disabilities: A Problem Area - Frost, Ruth; Frost, Barry P. (Canadian Journal of Counselling and Psychotherapy, 2012)
School counsellors in their daily work are faced with the investigation of children with "learning disabilities". This article attempts to delineate the major problems inthe area, which are those of definition, prevalence, aetiology and remediation, and to suggest ways out of the current "morass". Attempts at definition, ascertainment of prevalence, investigations of aetiology and remedial techniques based on hypothetical states are criticized and support is given for basing investigation and treatment on the presenting problem — usually reading or arithmetic. The basic tenets of remediation are reviewed and a realistic approach is outlined.